REFORMULASI TERHADAP UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 21 TAHUN 2007 TENTANG PEMBERANTASAN TINDAK PIDANA PERDAGANGAN ORANG BAGI PEMBERIAN HAK RESTITUSI PADA KORBAN TINDAK PIDANA PERDAGANGAN ORANG - Dita Febriyanti; Dessy Artina; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Fulfillment of rights of victims of acts criminal trafficking in persons in Indonesia is an important point in determining whether a country is progressing or not in the framework of social justice for all Indonesian people. The role is not only stated in the 1945 Constitution and Legislation. But more important is the implementation of the application and its implementation. After the enactment of Law Number 21 Year 2007 concerning Eradication of the Criminal Act of Trafficking in Persons is regulated in relation to the rights of victims in the form of compensation called restitution. The concept of liability compensation has also been regulated in important aspects of law enforcement. However, in practice, verdicts on cases of trafficking in persons rarely contain restitution. Reimbursement of costs to victims stated in Article 48 of Law Number 21 Year 2007 concerning the Criminal Act of Trafficking in Persons. However, in reality this right is sometimes not fulfilled on the grounds that from the level of investigation of victims there is no information obtained for example or at the level of prosecution the Public Prosecutor is not able to present evidence related that the loss suffered by the victim and even the court rarely makes decisions related to restitution against victims in Trafficking in Persons. Add moreThe purpose of this study is to find out the weaknesses related to the regulation of the fulfillment of victims' Restitution rights in the case of the Trafficking in Persons under the Law of the Republic of Indonesia Number 21 of 2007 concerning Eradication of the Criminal Act of Trafficking in Persons and determine a new formulation of the Law of the Republic of Indonesia Number 21 Year 2007 concerning the Eradication of Trafficking in Persons for the granting of restitution rights to victims in the case of Trafficking in Persons in the future. The research method used in this research is normative legal research (legal research) or also called library research, that is, research conducted with the normative juridical approach studied is literature or secondary data, and tertiary legal materials in accordance with the discussion of the titleThe problem in terms of weaknesses is why restitution is difficult to apply in the case of Trafficking in Persons, the author believes this is caused by regulations that need to be reformulated in relation to restitution rights, especially in the case of Trafficking in Persons where regulated restitution is formulated by forming a Law The law specifically regulates restitution in it because up to now there are many laws that regulate restitution making overlapping arrangements regarding restitution of victims.Keyword : Reformulation–Restitution Right–Crimina Act of Human Traffiking